Chromosome counts of some Zingiberaceous species from Thailand - Ladda Eksomtramage (Songklanakarin Journal of Science and Technology (SJST), 2002)
The data on chromosome numbers of 22 species belonging to 10 genera of Zingiberaceae distributed in Thailand were investigated. The somatic numbers range from 20 to 48 showing diploidy and polyploidy. Ten of these species are firstly reported here, i.e. Alpinia purpurata (Vielli) K. Schum. (2n = 48), Boesenbergia aff. rotunda (2n = 20), Cornukaempferia aurantiflora J. Mood & K. Larsen (2n = 46), Curcuma aff. oligantha Trimen (2n = 42), C. rhabdota Sirirugsa & M.F. Newman (2n = 24), Etlingera elatior (Jack.) R.M. Smith (white form) (2n = 48), E. hemisphaerica (Bl.) R.M. Smith (2n = 48), Hedychium gomezianum Wall. (2n = 34), H. longicornutum Bak. (2n = 34) and Zingiber aff. wrayi (2n = 22)